Efektivitas Home Visit dalam Pembinaan Akhlak Siswa Madarasah Ibtidaiyah - Ulfah, Emilya; Ariani, Lisna; Neny Qurrota A’yun (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
A home visiting is a program in the guidance and counseling service that is implemented at MI Raudhatul Jannah Martapura, to visit students' houses for completing the data, moral education, and to solve students’ problems in learning. The purposes of the study were (1) to find out the implementation of the home visiting at MI Raudhatul Jannah Martapura, (2) to find out student moral after the home visiting at MI Raudhatul Jannah Martapura, and (3) to know the effectiveness of the home visiting in student moral development at MI Raudhatul Jannah Martapura. The population in this study was 47 students, with a purposive sampling technique of 25 students in 8 and 9 grades. The data collection technique used questionnaires, interviews, and documentation. Then, data were analyzed with quantitative analysis techniques using the one-sample t-test. The results of this study showed that the effectiveness of home visiting at MI Raudhatul Jannah Martapura, based on the student moral is either